The vitamins : fundamental aspects in nutrition and health - Combs, Gerald F.; McClung, James P. (Elsevier/Academic Press, 2017)
"The Vitamins: Fundamental Aspects in Nutrition and Health, Fifth Edition, provides the latest coverage of the biochemistry and physiology of vitamins and vitamin-like substances. Health-related themes present insights into the use of vitamins, not only for general nutritional balance, but also as a factor in the prevention and/or treatment of specific health issues, such as overall immunity, inflammatory diseases, obesity, and anemia. Readers will gain an understanding of the roles vitamins play in gene expression and epigenetics, providing important information on the further development of personalized medical treatments that will also allow them to establish appropriate dietary programs based on individual genetic profiles. This cohesive, well-organized presentation of each vitamin includes key words, case studies, and coverage of the metabolic functions of appropriate vitamins. The readability of this complex content is highly regarded by students, instructors, researchers, and professionals alike."--Resumé vydavatele